Detection of flavonoids in microalgae from different evolutionary lineages. Issue 3 (12th May 2014) - Goiris, Koen; Muylaert, Koenraad; Voorspoels, Stefan; Noten, Bart; De Paepe, Domien; E Baart, Gino J.; De Cooman, Luc; Posewitz, M.
<x xml:space="preserve">Abstract</x> Flavonoids are important secondary plant metabolites believed to be present mainly in land plants. As phenolics were detected previously in microalgae using photometric assays, we wanted to investigate the nature of these phenolics and verify whether flavonoids are present. Therefore, in this study, we used state‐of‐the‐art ultra‐high performance liquid chromatography‐two‐dimensional mass spectrometry (UHPLC‐MS/MS) technology to investigate whether microalgae also contain flavonoids. For this, representative microalgal biomass samples from divergent evolutionary lineages (Cyanobacteria, Rhodophyta, Chlorophyta, Haptophyta, Ochrophyta) were screened for a set of carefully selected precursors, intermediates, and end products of the flavonoid biosynthesis pathways. Our data unequivocally showed that microalgae contain a wide range of flavonoids and thus must possess the enzyme pool required for their biosynthesis. Further, some of the microalgae displayed an intricate flavonoid pattern that is compatible with the established basic flavonoid pathway as observed in higher plants. This implies that the flavonoid biosynthesis pathway arose much earlier in evolution compared to what is generally accepted.